Odpowiedzi

2010-03-30T17:21:48+02:00
A) 2y = c +ab /:2
y = (c +ab) / 2

b) ay = b -dv / :a
y = (b -dv)/a

c) ay - 4ay = c-d
-3ay = c-d /: (-3a)
y = (c-d) / -3a

d) 3by-zza=2by
3by -2by = zza
by = zza /:b
y = zza/b
2 3 2
2010-03-30T17:25:31+02:00
A)
2y-ab=c
2y=c+ab
y=(c+ab)/2

B)
b=-ay+dv
ay=dv-b
y=(dv-b)/a

C)
ay-c=4ay-d
4ay-ay=d-c
3ay=d-c
y=(d-c)/3a

D)
3by-zza=2by
3by-2by=zza
by=zza
y=zza/b
1 5 1
  • bvbf
  • Początkujący
2010-03-30T17:31:50+02:00
A) 2y-ab = c
2y = c + ab /:2
y = (c + ab)/2

b) b = -ay+dv
ay = dv-b / :a
y = (dv-b)/a

c) ay-c=4ay-d
4ay-ay=-c+d
3ay=-c+d /:3a
y=(-c+d)/3a

d) 3by-zza=2by
3by-2by=zza
by=zza / :b
y= zza/b

1 3 1